Gambaran pewarnaan imunohistokimia p53 pada meningioma di Rumah Sakit Umum Pusat H. Adam Malik Medan - Donny dr; Adril Arsad Hakim; Iskandar Japardi; Sufida dr (Fakultas Kedokteran USU, 2013)
Intoduction : P53 is a protein produced by the TP53 gene, this protein is a major tumor suppression pathway of cells. P53 is a 'tumor suppressor gene' which is regarded as the protector of the gene. Although 'p53 pathway' are well known in the pathogenesis of these malignancies, its role in tumorigenesis of meningiomas is still very little understood.This study is intended to get an idea of how p53 expression by immunohistochemistry in patients with meningiomaMethod : The study was conducted with descriptive design. The data was patient’s demographic characteristics and data of tumors. The data was taken from the patient's General Hospital Haji Adam Malik began February 2010-February 2013, the immunohistochemical examination conducted in RS Murni Teguh Memorial.Result : Average patient age 41.2 (SD 11.78) years and mostly female by ratio of 2.3:1. Based on the location of the meningioma, the most common sequence is convexity meningiomas and parasagittal meningiomas (8 patients, 26.7%). Based on the results of histopathology, the highest frequency found was meningothelial type of meningioma by 17 cases (56.7%). Expression of p53 is found in 13.3% of patients who all have male sex. Expression of p53 is found in 25% of recurrent meningioma. Based on the index tumor edema, PTEI, found p53 expression by 50% in meningiomas with PTEI weight, 25% on PTEI moderate, and 5% on PTEI light.Conclusion : p53 expression is only found in the male gender (100%). Picture of p53 expression in recurrent tumors and tumors with a high index of edema seems to be the basis of further research to assess the relationship between these variables. Keywords : meningioma; p53